Cry8Ca2-containing layer-by-layer microcapsules for the pH-controlled release of crystal protein. (September 2014) - Li, Feng; Yan, Yue; Wang, Dandan; Zhang, Jie; Guo, Shuyuan
Abstract To extend the activity of crystal proteins by protection from environmental stress, we developed a new type of microcapsule containing Cry8Ca2 protoxins. Layer-by-layer (LbL) microcapsules containing Cry8Ca2 were successfully prepared for the first time by the alternate deposition of poly(acrylic acid) (PAH) and Cry8Ca2 at pH 6 on the surface of poly(styrene sulphonate) (PSS)-doped CaCO3 microbeads. Scanning electron microscopy (SEM) photos showed that microparticles were spherical in shape, approximately 2 μm in diameter. After removing the templates, the loading results were observed with a confocal laser scattering microscope (CLSM) by using fluorescein-labelled Cry8Ca2. The Cry8Ca2 protoxins were released from the microcapsules when they were exposed to a pH higher than 6 due to the loss of the electrostatic attraction. The microcapsules displayed resistance to proteinase K. Bioassay result demonstrated that the microcapsules with Cry8Ca2 displayed approximately equivalent insecticidal activity to the larvae of Anomala corpulenta compared to the free Cry8Ca2.